2005
DOI: 10.1016/j.neuron.2005.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Aβ42 Is Essential for Parenchymal and Vascular Amyloid Deposition in Mice

Abstract: Considerable circumstantial evidence suggests that Abeta42 is the initiating molecule in Alzheimer's disease (AD) pathogenesis. However, the absolute requirement for Abeta42 for amyloid deposition has never been demonstrated in vivo. We have addressed this by developing transgenic models that express Abeta1-40 or Abeta1-42 in the absence of human amyloid beta protein precursor (APP) overexpression. Mice expressing high levels of Abeta1-40 do not develop overt amyloid pathology. In contrast, mice expressing low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
455
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(487 citation statements)
references
References 41 publications
26
455
2
4
Order By: Relevance
“…In agreement with Aβ42 having higher hydrophobicity and higher toxicity than Aβ40 in vitro and in vivo, a large number of reports also show that Aβ42 contributes to synaptic dysfunctions [31][32][33][34] . Herein, we compared the toxicity of Aβ40, Aβ42 and Aβ43.…”
Section: Neural Toxicity and Amyloid Pathology Of Aβ43mentioning
confidence: 63%
See 1 more Smart Citation
“…In agreement with Aβ42 having higher hydrophobicity and higher toxicity than Aβ40 in vitro and in vivo, a large number of reports also show that Aβ42 contributes to synaptic dysfunctions [31][32][33][34] . Herein, we compared the toxicity of Aβ40, Aβ42 and Aβ43.…”
Section: Neural Toxicity and Amyloid Pathology Of Aβ43mentioning
confidence: 63%
“…Previous studies have elegantly demonstrated that Aβ42 is essential for amyloid deposition in vivo 31 and that Aβ40 inhibits this deposition 32 , based on the use of Bri-Aβ fusion proteins. The difference between Aβ40 and Aβ42 lies in the carboxyl-terminal amino-acid sequence, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation at 4 °C at 100,000 × g for 1 h, the supernatant was collected and stored at −80 °C until assayed. Brain samples were run in triplicate on ELISA plates coated with a monoclonal anti-Aβ1-16 antibody (kindly provided by Dr. William Van Nostrand, Stony Brook University, Stony Brook, NY) and detection was by monoclonal HRP conjugated anti-Aβ1-40 (MM32-13.1.1) and anti-Aβ1-42 (MM40-21.3.1) antibodies (kindly provided by Dr. Christopher Eckman, Mayo Clinic Jacksonville, Jacksonville, CA) [9,28,37]. For standards, Aβ1-40 and Aβ1-42 (Bachem California, Inc., Torrance, CA) were used after a pretreatment with HFIP to prevent fibril formation.…”
Section: Aβ Elisamentioning
confidence: 99%
“…In the AD brain, intracellular accumulation of hyperphosphorylated Tau aggregates and extracellular amyloid deposits comprise the two major pathological hallmarks of the disease (1,4). A␤ aggregation has been shown to initiate from A␤1-42, a peptide normally cleaved from the amyloid precursor protein (APP) via activities of ␣-and ␥-secretases (5,6). A large body of evidence in the past decade has indicated that accumulated soluble oligomers of A␤1-42, likely the earliest or intermediate forms of A␤ deposition, are potently toxic to neurons.…”
mentioning
confidence: 99%